2012
DOI: 10.1177/0094582x12441519
|View full text |Cite
|
Sign up to set email alerts
|

Swans, Conflicts, and Resonance

Abstract: A major legal reform of Chilean environmental institutions was approved in November 2009, at the end of Michelle Bachelet's administration. In sharp contrast with the external pressures that provided the impetus for the establishment of the country's environmental institutions in the early 1990s, this time the driving forces came mainly from an "internal demand," a broad social and political consensus about the need to improve the environmental framework. This consensus was a consequence of the institutional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…A closely related set of challenges has to do with the expectations and needs communities bring to participatory processes; when it comes to EIAs, most communities are the politically and economically weak party seeking to counter the proposals of powerful multinational corporations and their allies in government. Scholars have found that public participation procedures often fail to level the power asymmetries that characterize the relationships between developers, state agents and communities (Aguilar-Støen and Hirsch, 2017; Gregory, 2017; Li, 2015; Enríquez-de-Salamanca, 2018; Sepulveda and Villarroel, 2012;Londoño, 2008;Rodríguez-Becerra and Canal, 2008;Hurtado, 2002). Too often, participation is designed to convey information rather than integrate the community's input into the final decision.…”
Section: Participatory and Environmental Rights In Eiasmentioning
confidence: 99%
See 1 more Smart Citation
“…A closely related set of challenges has to do with the expectations and needs communities bring to participatory processes; when it comes to EIAs, most communities are the politically and economically weak party seeking to counter the proposals of powerful multinational corporations and their allies in government. Scholars have found that public participation procedures often fail to level the power asymmetries that characterize the relationships between developers, state agents and communities (Aguilar-Støen and Hirsch, 2017; Gregory, 2017; Li, 2015; Enríquez-de-Salamanca, 2018; Sepulveda and Villarroel, 2012;Londoño, 2008;Rodríguez-Becerra and Canal, 2008;Hurtado, 2002). Too often, participation is designed to convey information rather than integrate the community's input into the final decision.…”
Section: Participatory and Environmental Rights In Eiasmentioning
confidence: 99%
“…In both countries, activists and scholars have criticized public participation in EIAs as a sham process intended to legitimize development projects rather than give communities the power to reshape or veto projects (Sepulveda and Villarroel, 2012;Tecklin et al, 2011;Zárate Yepes, 2016;Rodríguez and Muñoz Ávila, 2009). Protests against new mine, energy and highway projects have become common as the pace of construction and extraction has quickened (Bury and Bebbington, 2013), and EIAs have become key sites of contentious politics (Hochstetler, 2011;Jaskoski, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Congress replaced a coordinating agency, the National Commission for the 35 Environment (Conama), with an Environment Ministry, an autonomous Environmental Impact Assessment (EIA) Agency, an enforcement agency, and specialized tribunals. Yet noted environmentalist-scholars have called the reforms 'a wasted opportunity' because public participation rights were insufficiently extended and decision-making, particularly in EIAs, remained 40 'politicized' (Sepulveda and Villarroel 2012). Chilean debates about how to depoliticize EIA decisions are an instance of the problem of legitimacy in a liberal democracy with strong neoliberal influences.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, Chilean authorities have made this choice through EIAs, a procedure by which the authorities evaluate one industrial project at a time to assess its environmental impacts and propose measures 100 to reduce, eliminate, mitigate or compensate those impacts. Critics complain that EIAs have promoted conflict because they are prone to political intervention and have fragmented Chilean environmental politics (Carruthers andRodriguez 2009, Sepulveda andVillarroel 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation